Non-union in forearm fractures - Jayakumar, P; Jupiter, J. B (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2014)
Non-union in forearm fractures is an uncommon but complex problem. This is especially given the unique anatomical structure and function of the forearm, making treatment distinctly different to that of other long bone fractures. Anatomical restoration of length, alignment, rotation and the radial bow maintains the optimal stabilising effects of the forearm muscles and interosseous membrane, as well as maximising the range of movement, particularly pronation and supination. Contemporary plate osteosynthesis using variations of the dynamic compression plate (DCP) developed by the AO group combined with established techniques of internal fixation have revolutionised the treatment of diaphyseal forearm fractures. Non-union rates have been minimised to below 5% and good to excellent functional outcomes are achieved. Non-union of the forearm is also intimately associated with a significant pain experience, marked pre-operative functional disability and physical and psychosocial morbidity. This review examines the literature and presents a guide to management as well as the current controversies and future directions related to this challenging problem.
Keywords: předloktí; nezhojené fraktury; fraktury ulny; Fractures, Ununited; Radius Fractures; Internal Fixators; Ulna Fractures; Postoperative Complications; lidé; Fracture Fixation, Internal; Practice Guidelines as Topic; Forearm; pooperační komplikace; fraktury vřetenní kosti; Humans; vnitřní fixace fraktury; směrnice pro lékařskou praxi jako téma; interní fixátory